Red and yellow, black and brown : decentering whiteness in mixed race studies - Rondilla, Joanne L.; Guevarra, Rudy P., Jr; Spickard, Paul R., 1950- (Rutgers University Press, 2017)
This book gathers together life stories and analysis by twelve contributors who express and seek to understand the often very different dynamics that exist for mixed race people who are not part white. Chapters focus on the social, psychological, and political issues and identities for people who are in dual or multiple minority situations.